PENGARUH PEMBERIAN PUPUK BOKASHI DAN NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays Var saccharata Sturt) - Robby Maulana AS; Husna Yetti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to determine the effect of bokashi fertilizer and NPK on growth and production of sweet corn. This research was conducted at the experimental farm of the Faculty of Agriculture, University of Riau, Pekanbaru from April 2014 to July 2014. The study was carried out experiments using a Randomized Block Design (RBD) factorial consisting of two factors: Bokashi and NPK fertilizer with 3 replications. Parameters measured were plant height, time of harvest, number of cobs per plot, the diameter of the cob without husk, cob length without husk, cob weight without husk, cob weight with husk, and production per plot. The results showed that the combination of Bokashi and NPK fertilizer application significanly affected the harvest age and numbers of cobs, bokashi fertilizer treatments significanly affected the diameter of the cob whitout husk and cob weight without husk whereas NPK fertilizer treatment significanly affected plant height, time of harvest, number of cob per plot and prodution per plot. Bokashi fertilizer application 15 ton/ha and 150 kg/ha NPK/ha can accelerategrowth and production of sweet corn.   Keywords: Sweet corn, bokashi fertilizer, NPK fertilizer